A noncommunication adaptive single phase auto-reclosure of transmission lines using phase space based criteria. (February 2018) - Khodabakhshi, F.; Sarlak, M.
Highlights: A set of phase space based criteria is proposed for auto-reclosure schemes. The present algorithm can distinguish between transient and permanent faults. The secondary arc extinction can be detected under different conditions. The presented algorithm is simple and can be embedded in reclosing relays. Abstract: This paper presents two phase space (PS) based criteria, and then on the basis of which it illustrates the preparation of a new non-intelligent and noncommunication adaptive single phase auto-reclosure (ASPAR) scheme to detect the secondary arc extinction for reclosure of transmission lines after self-clearing of transient faults. This scheme, which is fed by local voltage signal, can accurately distinguish between transient and permanent faults in transmission lines. Moreover, in the case of transient faults, the secondary arc extinction can be detected by the proposed algorithm within 8 ms and under effective operational and structural conditions, including different fault locations, load amounts, number of circuits, ideally transposed, partially transposed and un-transposed circuits, existence of shunt reactors and measurement noise. Besides, the presented PS based algorithm can be implemented sample by sample and does not need complicated integral computation, which connotes that it can be embedded in reclosing relays in transmission systems.